2019
DOI: 10.1093/nop/npz008
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-related neurocognitive dysfunction in patients with diffuse glioma: a retrospective cohort study prior to antitumor treatment

Abstract: Background Impairments in neurocognitive functioning (NCF) frequently occur in glioma patients. Both the tumor and its treatment contribute to these impairments. We aimed to quantify NCF in glioma patients before treatment and to investigate which factors influence NCF. Methods We performed a retrospective cohort study in diffuse glioma patients according to STROBE (Strengthening the Reporting of Observational Studies in Epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 28 publications
6
61
0
Order By: Relevance
“…In this work, we performed a retrospective cohort study with the aim to confirm the independent relationship between cognitive functioning in treatment-naive patients with diffuse gliomas (of all different grades) and survival, and to discuss the potential mechanisms that underly this relationship. We studied five predefined cognitive domains, with special focus on the domains executive functioning and memory; based on the high prevalence of impairments in these domains in glioma patients [3][4][5], we hypothesize that deficits in executive functioning and memory are most strongly related to survival in patients with diffuse glioma. Extensive domainspecific neuropsychological testing is more sensitive to these changes in cerebral network organization than MMSE and we, therefore, hypothesized that domain-specific scores from the extensive neuropsychological assessment are more strongly associated with survival than MMSE.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we performed a retrospective cohort study with the aim to confirm the independent relationship between cognitive functioning in treatment-naive patients with diffuse gliomas (of all different grades) and survival, and to discuss the potential mechanisms that underly this relationship. We studied five predefined cognitive domains, with special focus on the domains executive functioning and memory; based on the high prevalence of impairments in these domains in glioma patients [3][4][5], we hypothesize that deficits in executive functioning and memory are most strongly related to survival in patients with diffuse glioma. Extensive domainspecific neuropsychological testing is more sensitive to these changes in cerebral network organization than MMSE and we, therefore, hypothesized that domain-specific scores from the extensive neuropsychological assessment are more strongly associated with survival than MMSE.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their aggressive and heterogeneous features, DLGGs will inevitably lead to neurological deficits, albeit with relatively slow growth ( 1 , 2 ). According to reports, up to one-third of patients suffer from one or more deficits in neurocognitive domains, such as memory, attention, and executive function, which has a significant influence on quality of life ( 3 5 ). With the progression of medical technology, patients with DLGG tend to have prolonged survival, and their requirements are therefore even higher, being more concerned with neurocognitive function (NCF) than ever before ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is perhaps not surprising given our low-grade glioma frontal group was significantly younger than the other aetiology subgroups and individuals start to show age-related decline in processing speed as early as their 30s (Baxendale, 2011). Previous research examining cognition in glioma patients has also reported that processing speed is less impaired in low-grade compared to high-grade glioma, although this impairment was not specific to frontal lesions (Dehcordi, Mariano, Mazza, & Galzio, 2013;Miotto et al, 2011;van Kessel et al, 2019). While grouping patients with different aetiologies is likely to suffer from potential confounds, it remains necessary to obtain large groups of patients to investigate cognitive impairments (for similar approaches see Aridan, Pelletier, Fellows, & Schonberg, 2019;Aron, Monsell, Sahakian, & Robbins, 2004;Gläscher et al, 2012;Roca et al, 2010;Stamenova et al, 2017;Stuss et al, 2005;Thompson-Schill et al, 1998;Urbanski et al, 2016).…”
Section: Discussionmentioning
confidence: 70%